Comparative study of cytomorphological Robinson’s grading with modified Bloom-Richardson histopathological grading for breast carcinoma attending BPKIHS (Journal of Pathology of Nepal, 2025)
Background: Breast cancer is an impending public health problem for developing countries. Fine needle aspiration cytology is a minimally invasive technique that yields rapid results and is cost-effective. Robinson’s cytological grade is simple, easily reproducible, and correlates precisely with the Modified Bloom-Richardson histological grade, which is the gold standard. This study aims to compare Robinson’s cytological grade with the Modified Bloom-Richardson histological grade.Materials and Methods: This is a prospective study where 36 patients diagnosed with breast carcinoma cytologically and confirmed histologically were enrolled. The study was carried out from January 2021 to January 2022 in the Department of Pathology, B.P. Koirala Institute of Health Sciences. Comparison of Robinson cytological grade with Bloom Richardson histological grade was done using concordance rate and absolute concordance rate.Results: The concordance rates of Robinson’s cytological grades I, II, and III were 77.8%, 62.5% and 54.5% respectively. The absolute concordance rate was 63.89%. There was a significant correlation between Robinson’s cytological grade and Modified Bloom- Richardson histological grade (p value=0.001, Tb=0.493).Conclusions: It is possible to grade breast carcinoma on fine needle aspiration cytology preoperatively, as it corresponds well with histological grade. This would allow the assessment of the tumors without any surgical intervention, so that morbidity associated with overtreatment of low-grade tumors or undertreatment of high-grade tumors can be avoided.